Short-term event-driven analysis of the South-East Asia financial crisis: A stock market approach - Gerardo Gerry Alfonso Perez (Economies, 2021)
A systematic short-term event review of the major events in the South-East Asia Financial crisis is presented in this article. This analysis adds to the existing literature by focusing on the equity market, rather than on the foreign exchange market where there is already abundant literature, as well as going to a granular level with the hope that the analysis of the short-term market reactions can help policy-maker make appropriate decisions understanding the likely implications on the stock market. Short-term movements in the equity market might have very substantial economic impacts on investors and on the broad economy. The existing literature tends to focus on longer time horizons but from an equity investor point of view short-term fluctuations might be equally important or even more. When analyzing longer time horizons these short-term fluctuations, which might cause investors to fully unwind their positions or even bankruptcies, might be average out, underestimating the potential impact on the investor. Given these practical considerations it seems important to carry out a short-term event driven analysis of this crisis.
Keywords: 330; event driven; financial-crisis; South-East Asia